Family support and coping strategies among female inmates: a cross-sectional study in penitentiaries - Akmad Yanuar Fahmi Pamungkas; Yulifah Salistia Budi; Woro Nurul Seftianingtyas; Pipih Salanti; Tria Eni Rafika Devi; Muninggar Muninggar; Miftahul Hakiki; Muhammad Al Amin; Arni Nur Rahmawati; Prita Adisty Handayani; Rudiyanto Rudiyanto (Healthcare in Low-resource Settings, 2023)
Family is one of the closest people in helping individuals solve problems and serve as the foundation for developing coping strategies. Several factors influence coping strategies, including problem-solving skills and family support. This study aimed to explore the correlation between family support and coping strategies among female prisoners. The research employed a quantitative correlation design using a cross-sectional approach and a total sampling technique, with a sample of 33 female prisoners. The study included two variables: family support as the dependent variable and coping strategy as the independent variable. The chi-square test was used for data analysis. The results revealed that a majority of female prisoners received good family support (51.5%), and most of them used emotion-focused coping strategies (63.6%). The results indicate a significant correlation between family support and coping strategies for female prisoners, with a p-value of 0.004. It highlights the importance of family support for prisoners in developing effective coping strategies. The findings emphasize that family support plays a crucial role in enhancing coping strategies for inmates, ultimately contributing to an improved quality of life.